2019
DOI: 10.3390/su11195483
|View full text |Cite
|
Sign up to set email alerts
|

Asian Medicinal Plants’ Production and Utilization Potentials: A Review

Abstract: Medicinal plants research in Asia continues to receive significant national and international attention, particularly concerning its multiple roles in poverty alleviation and health care support. However, scientific information on the institutional arrangements, the potentials of different medicinal plants production systems, and the utilization methods, remain highly fragmented. This incomprehensive information base shades the development of a comprehensive research agenda to improve the current body of knowl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
63
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 125 publications
(65 citation statements)
references
References 238 publications
(270 reference statements)
0
63
0
2
Order By: Relevance
“…However, this study found that producers had second largest profit margins (25.9%) after the wholesalers (36.5%); but the price fluctuation was found a major threat for the economic potentiality of the products. Simlar findings was made for other medicinal and aromatic plants trade in the region (Astutik et al 2019). In order to increase the share of profit of producers/collectors, Maraseni et al (2006) and Pandit (2008) have recommended shortening the marketing channel of middlemen.…”
Section: Discussionmentioning
confidence: 99%
“…However, this study found that producers had second largest profit margins (25.9%) after the wholesalers (36.5%); but the price fluctuation was found a major threat for the economic potentiality of the products. Simlar findings was made for other medicinal and aromatic plants trade in the region (Astutik et al 2019). In order to increase the share of profit of producers/collectors, Maraseni et al (2006) and Pandit (2008) have recommended shortening the marketing channel of middlemen.…”
Section: Discussionmentioning
confidence: 99%
“…Traditional herbal medicines are rooted in indigenous knowledge systems. These cognitive systems play a crucial role in decision making with respect to the use of medicinal plants resources and are embedded in the lifestyle of the local community (Astutik and Kimengsi 2019). Xaxa (1999) opines that the notion of "indigenousness" is a political construction rather than an empirical reality.…”
Section: Indigenous People and Indigenousnessmentioning
confidence: 99%
“…Firstly, adequate management of medicinal plants and their traditional knowledge increases business opportunities in the field of medicine, which are expected to increase income (Andriamparany et al 2014;Mathibela et al 2015). Secondly, few businesses seek potential and traditional knowledge to use medicinal plants (Akankwasah et.al 2012;Astutik et al 2019). This is because the local and international business world is currently interested in traditional medicines based on plants and associated knowledge.…”
Section: Utilization Of Traditional Medicinal Plantsmentioning
confidence: 99%